Reforming the Basic Benefits Package in Armenia : Modeling Insights from the Health Interventions Prioritization Tool - Fraser, Nicole; Chukwuma, Adanna; Koshkakaryan, Marianna; Yengibaryan, Lusine; Hou, Xiaohui; Wilkinson, Tommy (World Bank, Washington, DC, 2021)
Armenia is an upper-middle-income (UMI) country in the South Caucasus region. The Coronavirus (COVID-19) pandemic and a regional crisis have resulted in the real economy's contraction following rapid growth in the past five years. Improving access to high-quality health care is essential for responding to non-communicable diseases (NCDs) and preventing mortality from infectious diseases in Armenia. Armenia is faced with the challenge of achieving Universal Health Coverage (UHC) when funding for health services faces downward pressures due to a donor funding transition, the Coronavirus (COVID-19) pandemic, and regional conflict. This report is part of the World Bank’s technical support toward universal health coverage in Armenia, which includes advisory services and analytics aimed at supporting the government’s efforts to expand access to high-quality health care. The report draws on the Health Interventions prioritization tool to optimize allocations across essential health services in the basic benefits package and estimate the potential impact of these allocations on population health.